PARENTAL COUNSELING FOR A BETTER PARENT-CHILD RELATIONSHIP - Breaz, A. (Problems of Engineer-Pedagogical Education, 2020)
Parenting is a newly developed field, because there are no schools and courses to teach you how to be a parent and how to educate your children to develop harmoniously and integrate into society. Permanent counseling is a method designed to help parents redefine their relationship with children, overcome existing communication difficulties and improve parenting skills. Parental counseling is presented as a broad configuration of actions / activities of guidance and guidance of parents. Specialized literature points to many articles related to parenting. The topics are very different: the psychology of parental control (Grolnik, 2003), family structure and school outcomes (Hatos, Baltatescu, 2013), parenting behavior to ensure success (Kalil, Dcleire, 2004); parenting and emotional development (Mercer, 2006), parental counseling (cuznetov, 2013) etc. The articles in the literature have been analyzed in the theoretical part of the article in order to highlight the stage in which the research is currently in progress. The purpose of the article is to present the results of our research among professionals and to enrich the literature in this field. The main objective of the research was to improve the parent-child relationship,The main objective was to improve the parent-child relationship with the help of parental counseling. The article includes a theoretical part with the problem data and the analysis of articles in the literature on this topic. The second part is the research consisting of: objectives and hypotheses, working methodology, studied batch, results and discussions, conclusions and references. The obtained results show a statistically significant improvement of the parent-child relationship following parental counseling. Our research can be a starting point for other future research that will also contribute in the field and help to develop techniques designed to improve parenting activity.